An assessment of the causes of accidents at RioZim’s Dalny mine in Chakari, Zimbabwe - Meya, Josephine (Midlands State University, 2020)
The research was carried out at Dalny mine with the aim of understanding the causes of accidents at the organisation. The objectives of the study included the identification of the causes of accidents, establishment of the trends on the occurrence of accidents at the mine and to evaluate the level of awareness of employees on the causes of accidents. A descriptive research design was used and a sample of 92 employees was selected. The research encompassed both qualitative and quantitative techniques and the use of primary and secondary methods for collecting valid and reliable data pertaining to the research. Primary data was obtained through questionnaires, field observations and interviews whilst secondary data was obtained from the organisations HSE records. Statistical Package for Social Sciences (SPSS) was used to analyse both quantitative and qualitative data. The major findings were that accidents at Dalny mine were caused by unsafe conditions and to a lesser extent by unsafe acts. The causes of such accidents were attributed to lack of adequate training on accident causal factors, poor standard working procedures, unrealistic production targets and ignorance to HSE issue. The research revealed that accidents negatively impact gold production at Dalny Mine as there are frequent stoppages of production operations. There is also a high rate of lost time and increased absenteeism. The study tested whether there is a significant relationship between level of education and employees knowledge on causes of accidents. Results indicated there is no significant relationship (p> 0.05; p=0.21) between level of education and employees knowledge on the causes of accidents. The study recommends that employees at Dalny mine need to attend courses on Safety, Health and Environment offered by organisations like NSSA so that they will be well versed in HSE issues. Safety, Health and Environmental standards like the OHSAS 18001 and ISO 9001 should be implemented in order to improve the safety system of Dalny mine. These recommendations were forwarded to the organisation so that they can have an accident free workplace.